Analysis of stationary systems with random parameters under stochastic influences - Блохін, Л. М.; Держак, С. В.; Сущенко, О. А. (Proceedings of National Aviation University (archive), 2021)
A new tool and spectral algorithms for practical analysis of the quality (accuracy) of a multidimensional dynamic system with random parameters at stochastic influences are considered. Algorithms are obtained as the result of a solution to a new problem statement